Treatment of Chronic Hepatitis C in Canadian Prison Inmates - John D Farley; Victor K Wong; Henry V Chung; Elizabeth Lim; Gavin Walters; Theresa A Farley; Eric M Yoshida (Canadian Journal of Gastroenterology)
PURPOSE: To assess sustained viral response rate and adherence to standard interferon alpha-2b and ribavirin therapy in inmates with chronic hepatitis C (HCV) in Canadian penitentiaries in the Pacific region.